2016
DOI: 10.3389/fpls.2016.00290
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome A Mediates Blue-Light Enhancement of Second-Positive Phototropism in Arabidopsis

Abstract: Hypocotyl phototropism of etiolated Arabidopsis seedlings is primarily mediated by the blue-light receptor kinase phototropin 1 (phot1). Phot1-mediated curvature to continuous unilateral blue light irradiation (0.5 μmol m−2 s−1) is enhanced by overhead pre-treatment with red light (20 μmol m−2 s−1 for 15 min) through the action of phytochrome (phyA). Here, we show that pre-treatment with blue light is equally as effective in eliciting phototropic enhancement and is dependent on phyA. Although blue light pre-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…Interestingly, a recent study found that curvature enhancements stemming from red-or bluelight pretreatments were affected by light intensity, where higher fluence rates of the directional light caused a reduction in phototropic curvature (Sullivan et al 2016). It is possible that enhancement of phototropic curvature was not observed in this case due to fluence rates that were high enough to inhibit the enhancement of curvature.…”
Section: Phototropic Responses In Hypocotylsmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, a recent study found that curvature enhancements stemming from red-or bluelight pretreatments were affected by light intensity, where higher fluence rates of the directional light caused a reduction in phototropic curvature (Sullivan et al 2016). It is possible that enhancement of phototropic curvature was not observed in this case due to fluence rates that were high enough to inhibit the enhancement of curvature.…”
Section: Phototropic Responses In Hypocotylsmentioning
confidence: 88%
“…These results are not unexpected, as the previous studies of Arabidopsis have shown that etiolated (dark-grown) seedlings exposed to red-light pretreatment experience an increase in the bluelight phototropic response (Sakai and Haga 2012;Goyal et al 2013). In addition, recent studies have demonstrated that overhead pretreatment with blue-light illumination also enhances the phototropic response (Sullivan et al 2016). It has been proposed that this effect is due to red, far red, and blue light all acting together as an activator of phytochrome A, which leads to enhancement of the phototropic response (Lariguet and Fankhauser 2004).…”
Section: Phototropic Responses In Rootsmentioning
confidence: 99%
“…Phytochromes are not essential for phototropism, but they enhance growth in the direction of light (Strasser et al 2010). Phytochrome A is required for enhancement of phototropism by pretreatment with FR and B and also promotes phototropic growth in response to pre-irradiation with R (Parks et al 1996;Janoudi et al 1997;Stowe-Evans et al 2001;Kirchenbauer et al 2016;Sullivan et al 2016). Tissue-specific expression has shown that this response is mediated by mesophyll-localized phyA (Kirchenbauer et al 2016).…”
Section: Phytochrome a Suppresses Gravitropism And Promotes Phototropmentioning
confidence: 99%
“…PhyA ‐deficient mutants of Arabidopsis do not exhibit strong growth or developmental defects when grown under controlled environmental conditions (Reed et al ). However, PhyA plays important roles under specific light conditions: seed germination, seedling de‐etiolation, shade avoidance responses (Yanovsky et al ; Krzymuski et al ), phototropic stimulation under low light intensities (Sullivan et al ), and in the induction of early response genes during dark‐to‐light transitions (Tepperman et al ). Moreover, Dalchau et al () proposed that both clock‐regulated blue and red light signaling are required for the maintenance of the appropriate Ca 2+ ions rhythms in the cytosol ([Ca 2+ ] cyt ), which are important for stomatal opening.…”
Section: Discussionmentioning
confidence: 99%
“…PhyA-deficient mutants of Arabidopsis do not exhibit strong growth or developmental defects when grown under controlled environmental conditions (Reed et al 1994). However, PhyA plays important roles under specific light conditions: seed germination, seedling deetiolation, shade avoidance responses (Yanovsky et al 1995;Krzymuski et al 2014), phototropic stimulation under low light intensities (Sullivan et al 2016), and in the induction of early response genes during dark-to-light transitions (Tepperman et al 2001 Figure S8). However, irPhyA plants lacked a gated response to light in the night, which suggests that NaPhyA enables plants to gate photosynthetic responses to red-light signals in a time-specific manner.…”
Section: Discussionmentioning
confidence: 99%